Designing and evaluating a persuasive child restraint television commercial. (2nd April 2016) - Lewis, Ioni; Ho, Bonnie; Lennon, Alexia
ABSTRACT: Objective: Relatively high rates of child restraint inappropriate use and misuse and faults in the installation of restraints have suggested a crucial need for public education messages to raise parental awareness of the need to use restraints correctly. This project involved the devising and pilot testing of message concepts, filming of a television advertisement (the TVC), and the evaluation of the TVC. This article focuses specifically upon the evaluation of the TVC. The development and evaluation of the TVC were guided by an extended theory of planned behavior that included the standard constructs of attitudes, subjective norms, and perceived behavioral control as well as the additional constructs of group norms and descriptive norms. The study also explored the extent to which parents with low and high intentions to self-check restraints differed on salient beliefs regarding the behavior. Methods: An online survey of parents ( N = 384) was conducted where parents were randomly assigned to either the intervention group ( n = 161), and therefore viewed the advertisement within the survey, or the control group ( n = 223), and therefore did not view the advertisement. Results: Following a one-off exposure to the TVC, the results indicated that, although not a significant difference, parents in the intervention group reported stronger intentions ( M = 4.43, SD = 0.74) to self-check restraints than parents in the control group ( M = 4.18, SD = 0.86). In addition, parents in the intervention group ( M = 4.59, SD = 0.47) reported significantly higher levels of perceived behavioral control than parents in the control group ( M = 4.40, SD = 0.73). The regression results revealed that, for parents in the intervention group, attitudes and group norms were significant predictors of parental intentions to self-check their child restraint. Finally, the exploratory analyses of parental beliefs suggested that those parents with low intentions to self-check child restraints were significantly more likely than high intenders to agree that they did not have enough time to check restraints or that having a child in a restraint is more important than checking the installation of the restraint. Conclusion: Overall, the findings provide some support for the persuasiveness of the child restraint TVC and provide insight into the factors influencing reported parental intentions as well as salient beliefs underpinning self-checking of restraints. Interventions that attempt to increase parental perceptions of the importance of self-checking restraints regularly and brevity of the time involved in doing so may be effective.